BINNER ETHICAL AJARAN SOSROKARTONO DALAM PERSPEKTIF HERMENEUTIKA - yono, Mul (Faculty of Humanities, Diponegoro University, 2014)
Abstract This paper seeks to interpret and seek relevance of Sosrokartonoâ€™s moral teachings, especially those expressed in the binner ethical form, for the life of Indonesian people in the present. Binner ethical in the moral teaching is discovered in Javanese culture. To be able understand the moral teaching need interpretation in depth, not only use ability to reason but also the using ability of â€œrasa-pangrasaâ€.The Sosrokartonoâ€™s binner ethical, as well as other moral teachings, still based on Sosrokartonoâ€™s philosophy of life that emphasized the obligation of human life to serve and devote themselves to God Almighty trough the help and helping fellow humans in need without strings attached, on the basis of principle â€œleladi mring sesamiâ€.The Sosrokartonoâ€™s moral teachings have relevance for the formation of Indonesian national character, which is currently demoralized. The Sosrokartonoâ€™s moral teachings are very concerned with inner strength to counteract the development of the character of individualistic, materialistic, hedonistic and secularistic on Indonesian peoples, which currently is beset by modernization and globalization. Key words: moral teaching, binner ethical, interpretation, relevance, counteract, modernization and globalization, Indonesian national character Â